2012
DOI: 10.4304/jltr.3.1.102-111
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Problems of Teaching and Learning English in the Isfahan Province High Schools, Iran

Abstract: Abstract-This study basically aimed at identifying the problems of teaching and learning English in the high schools of Isfahan, Iran. The data needed for the study were extracted from the standardized questionnaires given to 200 randomly selected students from the high schools of Isfahan and their English teachers constituting the two groups of participants in this study. The instruments used to gather the data were two closed questionnaires, one for the students and the other one for the teachers. The questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…The problems Iranian learners of English have in learning English have often been raised at conferences and seminars in Iran and are generally attributed to obvious and well-documented factors such as the limited time available for English instruction in schools, issues related to the curriculum, tests, teaching resources, teacher competence, teacher and learner motivation as well as to lack of opportunities to use English outside of the classroom (Abbasi et al, 2009;Behroozi and Amoozegar, 2014;Fariadian et al, 2014;Tabatabaei and Pourakbari, 2012). For instance, Behroozi and Amoozegar's survey study with 180 EFL teachers coming from 150 schools indicated that English teachers' low proficiency in English, lack of technological resources at schools and insufficient teaching time are some of the factors responsible for the ineffective English education system in Iran.…”
Section: Reconsidering the Problem Of Teaching Spoken English In Iranmentioning
confidence: 99%
“…The problems Iranian learners of English have in learning English have often been raised at conferences and seminars in Iran and are generally attributed to obvious and well-documented factors such as the limited time available for English instruction in schools, issues related to the curriculum, tests, teaching resources, teacher competence, teacher and learner motivation as well as to lack of opportunities to use English outside of the classroom (Abbasi et al, 2009;Behroozi and Amoozegar, 2014;Fariadian et al, 2014;Tabatabaei and Pourakbari, 2012). For instance, Behroozi and Amoozegar's survey study with 180 EFL teachers coming from 150 schools indicated that English teachers' low proficiency in English, lack of technological resources at schools and insufficient teaching time are some of the factors responsible for the ineffective English education system in Iran.…”
Section: Reconsidering the Problem Of Teaching Spoken English In Iranmentioning
confidence: 99%
“…In terms of facilities, we cannot leave aside the role of library as the heart of an institution is very vital. As a research from Tabatabaei (2013) proven that where a library at a school cannot provide proper learning sources it will become one of reasons of students' failure in learning such as teachers will use textbook which is not suitable for students' level. In short, this matter also needs to be highlighted by school management as it is one of potential places for students to reinforce what they learn in classroom.…”
Section: Common Problems Faced By Lower Level Students In Learning Enmentioning
confidence: 99%
“…Moreover, teachers also often deal with big classes their lack of capability in operating audio visual media or any simple teaching aid (Tabatabaei, 2013;Riyaz & Mullick, 2016). In this context, public schools including in Indonesia usually consist of thirty to forty students in one class.…”
Section: Introductionmentioning
confidence: 99%
“…The creative ability of (English) language teacher helps him/her to make optimum utilization of available teaching and learning resources for promoting communicative competence among the students. The creative teachers use multiple instructional techniques (and technologies) and resources in promoting the communicative abilities of the learners (Tabatabaei & Pourakbari, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%